Plant Diversity in Protected Area of IUPHHK-HT PT. Wana Hijau Pesaguan in Province West Kalimantan - Istomo Istomo; Khalid Hafazallah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Protected area in plantation forest should be managed properly in order to sustainable development. One of the initial steps of the protected area management is by knowing the level of plant diversity which composing the community of its vegetation. The aim of this research is to measure plant diversity in protected area of IUPHHK-HT PT. Wana Hijau Pesaguan in Province West Kalimantan. Vegetation analysis is done at riverbanks, slope area more than 40% and conservation area of biodiversity. The result is that there are found 295 species of plants consisting 222 trees, 32 under storey plants, 38 lianas and 3 epiphytes. Shannon-Wiener diversity index (H’) values of trees with anystage of growth are about 3.02–4.41, which classified as high level of diversity. Under storey plants and lianas have H’ values about 1.00-3.22 which classified as mid level diversity. The diversity level of epiphytes are low to mid, with H’ values 0-1.04. Similarity Index value between all locations are low (less than 75%) except for epiphytes, which only in conservation area of biodiversity had different epiphytes composition comparing to the other sites. Key words: plant diversity, plantation forest, protected area, West Kalimantan